A Rapid and Quantitative HPLC Method for Determination of Diethylene Glycol - van Rooyen, T.J.; van Wyk, C.J. (South African Journal of Enology and Viticulture, 2017)
A method was developed for determining diethylene glycol (DEG) by HPLC. Good separation was achieved by analysis of standard mixtures containing normal wine components and DEG. Addition of DEG to wine samples proved that DEG did not elute with any of the known constituents. Recovery studies proved the method to have a good repeatability. A selection of South African and imported wines were analysed and it was found that none contained any DEG.